The non-technical challenges of Location Based Services markets: are the users' concerns being ignored? - Basiri, Anahid; Moore, Terry; Hill, Chris; Bhatia, Paul (2016)
Location Based Services (LBS) market is growing rapidly, however it has faced several challenges and issues, including the availability of reliable positioning services seamlessly (indoors and outdoors), the privacy protection issues, and the relatively high demands for resources, such as high power consumption and cost. Among all the issues introduced to the markets of LBS, the non-technical issues can be easier to understand for many of ordinary users of LBS and they, consequently, can become yet bigger challenge to the development of LBS markets. Lack of social acceptance of the LBS applications can result in slowing down the growth of the market, if not failure. This paper reviews the non-technical issues of LBS market from users’ perspective and evaluate the significance of their impact on the growth of the market based on the results of a survey conducted and the predictive analysis have been done.